Ragam Riwayat dan Tafsir Kisah Sulaiman dalam Al-Dakhil Fi Al-Tafsir
Many of the history of Isra>i’liyat enter the world of interpretation, especially in the verses that explain the stories of the Prophets. The story of Prophet Sulayman As is one of the stories in the Koran which in its interpretation is infused with the story of Isra>’iliyat so that it tarnishes the interpretation of the verses of the story. From there the researcher is interested in tracing these deviations in order to purify the interpretation so that it becomes clear between al-As